Homologation of the Olympic ski stadiums as the basis for the requirements for the technical, tactical and functional training of cross country athletes - Khmelnytska, Y.; Kropta, R.; Hruzevych, I.; Kormiltsev, V.; Yefanova, V.; Smirnova, Z.; Tron, R.; Hudzevych, L. (Journal of Physical Education and Sport, 2020)
The article is devoted to the analysis of the homologous characteristics of the Olympic ski tracks as the basis for the requirements for the technical, tactical and functional preparation process of the ski athletes.There is known fact, that the effectiveness of competitive activities in the ski races is largely dependent on the homologous characteristics of ski tracks, imposing certain requirements to the functionality level of the athletes, the election of athletes of the running technique and tactics of overcoming the competitive distance. During the research, we havefoundedthe connection of homologous characteristics with the results of competitions at the different distances of ski races. The analysis of the correlation straps of the homologous characteristics of the tracks with the speed and density of the results of the competitions showed that the leading ski athletes of the world on the speed of the race is most affected by the sum of height differences (r = 0.37), the number of laps in the distance (r = 0.26), and length of maximum lifting (r = 0.25), whereas the density of the results in the race is influenced by the length of the lap of the sporting distance (r = 0.48).We were determined the speed characteristics of the modern ski races. The average speed in skiing is about 6-7 m·sec-1depending on the race settings. During the ski running with increasing distance, there is a progressive decrease in the average speed. Thus, the best ski athletes in the world overcome the marathon distance (30 km) by an average of 19% slower than the distance of 5 km, and the distance of 10 km - by 5-7% slower. This is due to the fact that the organizers of the competition, use for laying long lines of the ski track areas with a smaller height difference.